2011
DOI: 10.1182/blood-2011-03-341222
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin is a determinant of metastasis through a mechanism linked to the thrombin binding domain but not the lectin-like domain

Abstract: and 5 BloodCenter of Wisconsin, Milwaukee, WI Thrombomodulin (TM) is a predominantly endothelial transmembrane glycoprotein that modulates hemostatic function through a domain that controls thrombinmediated proteolysis and an N-terminal lectin-like domain that controls inflammatory processes. To test the hypothesis that TM is a determinant of malignancy and dissect the importance of these functional domains in cancer biology, metastatic potential was evaluated in TM Pro mice expressing a mutant form of TM with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 38 publications
(80 reference statements)
2
82
1
2
Order By: Relevance
“…This is illustrated by studies demonstrating endothelial cell expression of TF in invasive breast cancer (42) or the impact of their genetic status on their anticoagulant potential (43). It remains to be studied whether TF trafficking from mesenchymal cancer cells to endothelium could produce similar effects and contribute to thrombosis or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated by studies demonstrating endothelial cell expression of TF in invasive breast cancer (42) or the impact of their genetic status on their anticoagulant potential (43). It remains to be studied whether TF trafficking from mesenchymal cancer cells to endothelium could produce similar effects and contribute to thrombosis or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice partially deficient in prothrombin have significantly diminished in vivo metastasis of Lewis lung carcinoma. 29 Many studies have demonstrated, through PAR-1 and other thrombin effector mechanisms, that thrombin directly promotes tumor cell proliferation, adhesion to platelets, production of endothelial cells, matrix proteins, and vascular endothelial growth factor A (VEGF-A) to support angiogenesis. 3 Fibrin appears to be important in this process, as fibrinogen-deficient mice also have diminished in vivo metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…50 This concept recently found even more support in a report on the pro-metastatic phenotype of mice with a thrombomodulin mutant with decreased affinity for thrombin. 51 Further evidence for a prominent role of downstream coagulation activation in metastasis comes from experiments in genetically modified mice that lack platelets, PAR4, or fibrinogen. Mice with either of these genetic modifications were protected from metastasis, which provides evidence that metastasis is facilitated by thrombinactivated platelets via PAR4.…”
mentioning
confidence: 99%